Proposing Hybrid Architecture to Implement Cloud Computing in Higher Education Institutions Using a Meta-synthesis Appro - hamid reza bazi; ali moeini; alireza hasanzadeh (Journal of Information Technology Management)
Cloud computing is a new technology that considerably helps Higher Education Institutions (HEIs) to develop and create competitive advantage with inherent characteristics such as flexibility, scalability, accessibility, reliability, fault tolerant and economic efficiency. Due to the numerous advantages of cloud computing, and in order to take advantage of cloud computing infrastructure, services of universities and HEIs need to migrate to the cloud. However, this transition involves many challenges, one of which is lack or shortage of appropriate architecture for migration to the technology. Using a reliable architecture for migration ensures managers to mitigate risks in the cloud computing technology. Therefore, organizations always search for suitable cloud computing architecture. In previous studies, these important features have received less attention and have not been achieved in a comprehensive way. The aim of this study is to use a meta-synthesis method for the first time to analyze the previously published studies and to suggest appropriate hybrid cloud migration architecture (IUHEC). We reviewed many papers from relevant journals and conference proceedings. The concepts extracted from these papers are classified to related categories and sub-categories. Then, we developed our proposed hybrid architecture based on these concepts and categories. The proposed architecture was validated by a panel of experts and Lawshe’s model was used to determine the content validity. Due to its innovative yet user-friendly nature, comprehensiveness, and high security, this architecture can help HEIs have an effective migration to cloud computing environment.